Deformation and sedimentary evolution of the Lake Albert Rift (Uganda, East African Rift System). (September 2017) - Simon, Brendan; Guillocheau, François; Robin, Cécile; Dauteuil, Olivier; Nalpas, Thierry; Pickford, Martin; Senut, Brigitte; Lays, Philippe; Bourges, Philippe; Bez, Martine
Abstract: This study proposed a new reconstruction of the tectono-sedimentary evolution of the Lake Albert Rift based on a biostratigraphical, sedimentological and structural re-evaluation of the outcropping data and on an exceptional subsurface dataset. The infilling of the rift consists of lacustrine deposits wherein two major unconformities dated at 6.2 Ma and 2.7 Ma were characterized, coeval with major subsidence and climatic changes. Combined with the fault analysis, the evolution and distribution of the subsidence highlights a four-steps evolution of the rift after its initiation dated at 17.0 Ma. The first phase (17.0 – 6.2 Ma) consists of low and diffuse extension associated with low accommodation rates ranging from 150 to 200 m/Ma. Restricted in the southern part of the basin, the depocenter location is poorly controlled by faults, meaning that the basin extension was potentially larger at this time. The second time interval (6.2 – 2.7 Ma) shows an increase of accommodation rates with values reaching more than 800 m/Ma. These high rates combined with the location of the major depocenters down the bounding faults argue for a first true rifting phase. Between 2.7 Ma and 0.4 Ma, the accommodation rates decreases to reach less than 400 m/Ma and the individualization of major depocenters continue down the major fault in the southern and northwestern parts of the basin. Finally, between 0.4 Ma and present-day, a late uplift led the formation of the Ugandan scarp. Comparison of the Lake Albert Rift evolution with the data available in the rifts of both branches of the East African Rift System shows that most of the sedimentary basins experienced the same geometrical evolution from large basins with limited fault control during Late Miocene to narrow true rift in Late Pleistocene. Graphical abstract: Highlights: Deposition in the Lake Albert Basin began at 17 Ma, older than the Late Miocene age previously mentioned. Infilling consists to sub-aquatic lacustrine deposits showing unconformities related to subsidence and climatic changes. Three-steps evolution: diffuse extension (17–6.2 Ma), rifting phase 1 (6.2–2.7 Ma), rifting phase 2 and uplift (2.7–0 Ma).and